(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Sediment transport is the movement of organic and inorganic particles caused by gravity, a moving fluid’s force, the wind, and ice motion. Sediment deposition degrades dams’ safety, leading to environmental pollution and channel area reduction. This study describes the effect of the weir height and spacing of used and non-used rectangular configuration structures on sediment transport rates in an open channel. This project was created using a rectangular open channel (30 cm wide and 60 cm deep). A sharp-crested weir was installed in the channel, and the rectangular wooden configurations were fixed in specific locations on each weir to reduce the bedload transportation rate and sediment motion. The weir heights were different (0.25B, 0.35B, 0.45B, and 0.55B, where B is the channel width). Also, the spacing between the baffle blocks (S) was set to 4Y, 8Y, 12Y, and 16Y, where Y was the maximum water depth without installing blocks and weirs. The results showed that the maximum transported bedload for the lowest weir was 1.4 kg/min, but only 4.4 × 10-3 kg/min was transported for the weir 16.5-cm high with baffle blocks. Using long baffle blocks yielded a worse result than using no blocks. The sediment-transport rate increased to 1.66 kg/min for the 7.5-cm weir due to block configurations. In conclusion, the obtained result contradicts the predicted result, as using baffle blocks increased the sediment transportation rate.